(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the development of volitional qualities and its significant aspects in future physical education teachers on the basis of a competency approach. At the same time, the task of the development of volitional qualities in teachers of physical education in the framework of pedagogical sciences, the methodology of training personnel were analyzed.